2014
DOI: 10.1515/secm-2014-0040
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of basalt FRP bars in alkaline environment

Abstract: This paper investigates the degradation of basalt fiber reinforced polymer (BFRP) bars used for concrete construction in an alkaline environment. The relationships between tensile strength, elastic modulus, shear strength and moisture absorption rate over time are analyzed using a tension test, short-beam test and moisture absorption weighting. The tensile strength degradation of BFRP bars was further compared with that of Glass FRP (GFRP) bars in the literature. The results indicated that BFRP bars exhibit re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…Numerous researches have been carried out on mechanical properties and bond durability of BFRP bars or BFRP reinforced concrete [11][12][13][14]. The tensile strength loss of BFRP bars was as high as 40% after immersion in 55 ∘ C alkaline solution for 63 days [11], and the bond strength of BFRP bars in concrete immersed in artificial seawater for 90 days exhibited a 25% reduction [12]. Tighiouart et al [13] confirmed that it was easy bleeding at the interface between BFRP bars and concrete when the large diameter BFRP bars were used, resulting in a decreased bond strength between BFRP bars and concrete.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous researches have been carried out on mechanical properties and bond durability of BFRP bars or BFRP reinforced concrete [11][12][13][14]. The tensile strength loss of BFRP bars was as high as 40% after immersion in 55 ∘ C alkaline solution for 63 days [11], and the bond strength of BFRP bars in concrete immersed in artificial seawater for 90 days exhibited a 25% reduction [12]. Tighiouart et al [13] confirmed that it was easy bleeding at the interface between BFRP bars and concrete when the large diameter BFRP bars were used, resulting in a decreased bond strength between BFRP bars and concrete.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the bond-slip behavior of BFRP bars in concrete was different from that of steel bar [16,17]. Although some achievements about the bond-slip behavior between BFRP bars and concrete have been made [11,[16][17][18][19][20][21][22][23][24], most of them were focused on small size BFRP bars (<B 10 mm). However, the bond-slip behavior between large size BFRP bars and concrete is different due to larger interfacial transition zone, internal bleeding, and smaller specific perimeter.…”
Section: Introductionmentioning
confidence: 99%
“…As summarized in Figure 8(c), the shear strength of the basalt–neat epoxy composite laminate is calculated as 36.1 MPa before the seawater aging which is comparable with the literature. 3840 The addition of 2 wt% HNTs in the epoxy matrix is found to increase the shear strength up to 42.9 MPa, which is approximately 19% higher than that of the control sample. It is clear that the ILSS decreases gradually with the increasing aging time, and the reduction in ILSS for the neat basalt–epoxy and the hybrid composite is calculated as 52.3 and 39.5%, respectively, after six-month seawater aging.…”
Section: Resultsmentioning
confidence: 95%
“…As shown in Figure 3(a), the surface condition of the bar changes after 63 days of immersion in the alkaline solution at 32°C. The surface of the bar is corroded, as suggested by Wu et al, 39 due to etching. Similarly, in Figure 3(b)-(d), it can be seen that the depth of corrosion has accelerated to a greater extent with the increase in exposure temperature.…”
Section: Results and Discussion For Degradation Rate-based Modelmentioning
confidence: 95%